The Dynamics of The Democratic Process In Legal Politics In Indonesia And Egypt - Nahrowi Nahrowi; Masyrofah Masyrofah; Nurul Handayani (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe implementation of democratic systems in several Muslim countries has obstacles. This is due to the development of people's thinking patterns about understanding democracy itself. Islam as a religion emphasizes the establishment of harmonious relations, but when applying the relationship of Islam and democracy in the life of the state does not necessarily be smooth at the level of practice. But on the other hand, It faced with the reality of the problems in implementing democratization in the Islamic world. Some countries claimed to succeed as democratic countries, generally after going through a transition period of transfer of government power. But on the contrary, not a few countries that have not or are not ready to accept change as a process of democratization are trapped in the struggle for power and lead to conflict and violence. Therefore it is important to discuss the challenges and obstacles of democratization in the Islamic world. With a normative-empirical approach, this article aims to analyze the problems of the democratization process in two Muslim countries, namely Indonesia and Egypt. This study found that the process of democratization as a part of the legal-political system in Muslim countries must adapt to the culture and political conditions of each country. The challenges of the democratization process in Indonesia and Egypt, namely the media, ideology, natural resources, common vision and mission in developing the country, strong commitment from all components of the nation, the political will of the head of state related to power-sharing and strengthening dialogue with the people.Keywords: Democracy, Muslim Countries, Conflict of Power, Legal Politics Abstrak Penerapan sistem demokrasi di beberapa negara muslim memiliki kendala. Hal ini disebabkan semakin berkembangnya pola pemikiran masyarakat mengenai pemahaman demokrasi itu sendiri. Islam sebagai agama yang menitikberatkan kepada terjalinnya hubungan yang harmonis dalam kehidupan bernegara, namun ketika menerapkan hubungan Islam dan demokrasi dalam kehidupan bernegara tidak serta merta mulus pada tataran praktiknya. Idealnya sebuah negara yang menjalankan sistem demokrasi memiliki tingkat partisipasi masyarakat yang kian meningkat dalam turut serta membangun negara. Namun di sisi lain dihadapkan pada realitas adanya problematika dalam menerapkan demokratisasi di dunia Islam. Ada negara yang diklaim berhasil sebagai negara demokratis, umumnya setelah melewati masa-masa transisi perpindahan kekuasaan pemerintahan. Namun sebaliknya, tidak sedikit negara yang belum atau tidak siap menerima perubahan sebagai proses demokratisasi justru terjebak dalam perebutan kekuasaan dan berujung kepada konflik dan kekerasan. Oleh karena itu penting untuk dibahas tentang apa saja tantangan dan hambatan demokratisasi di dunia Islam. Dengan pendekatan normatif-empiris, artikel ini bertujuan untuk menganalisa problematika proses demokratisasi di dua negara Muslim yaitu Indonesia dan Mesir. Studi ini menemukan bahwa proses demokratisasi yang merupakan bagian dari sistem politik hukum di negara muslim haruslah menyesuaikan dengan kultur dan kondisi politik masing-masing negara tersebut.Kata Kunci: Demokrasi, Negara Muslim, Media, Konflik Kekuasaan, sistem hukum ketatanegaraan АннотацияВнедрение демократической системы в нескольких мусульманских странах сталкивается с препятствиями. Это связано с развитием у людей образов мышления в отношении понимания самой демократии. Ислам, как религия, подчеркивает установление гармоничных отношений в государственной жизни, однако практически применение исламских и демократических отношений в жизни государства не обязательно гладко. В идеале страна, в которой действует демократическая система, дожна иметь все более высокий уровень участия общественности в строительстве страны. Однако, с другой стороны, существуют проблемы в применении демократизации в исламском мире. Есть страны, которые считаются успешными как демократические страны, как правило, после завершения переходного периода передачи государственной власти. Напротив, многие страны, которые не готовы или не готовы принять перемены как процесс демократизации, попадают в ловушку борьбы за власть и приводят к конфликтам и насилию. Поэтому важно обсудить, какие существуют проблемы и препятствия на пути демократизации в исламском мире. Данная статья с нормативно-эмпирическим подходом направлена на анализирование проблем процесса демократизации в двух мусульманских странах, а именно Индонезии и Египте. Это исследование показывает, что процесс демократизации, который является частью правовой политической системы в мусульманских странах, должен адаптироваться к культуре и политическим условиям каждой страны.Ключевые слова: Демократия, Мусульманское Государство, Сми, Конфликт Власти, Конституционно-Правовая Система.